Black students applying and admitted to medicine in the province of Quebec, Canada: what do we know so far? - Leduc, Jean-Michel; Kpadé, Victoire; Bizimungu, Samantha; Bourget, Martine; Gauthier, Isabelle; Bourdy, Christian; Chétrit, Estelle; Razack, Saleem (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2021)
To address the underrepresentation of Black students in medical schools in Canada and identify barriers in selection processes, we compare data from the latest Canadian census to that of an exit-survey conducted after a situational judgment test (Casper) among medical school applicants and from questionnaires done after selection interviews in Quebec, Canada. The proportion of Black people aged 15-34 years old in Quebec in 2016 was 5.3% province-wide and 8.2% in the Montreal metropolitan area. The proportion in the applicant pool for 2020 in Quebec was estimated to be 4.5% based on Casper exit-survey data. Comparatively, it is estimated that Black people represented 1.8% of applicants invited to admission interviews and 1.2% of admitted students in Quebec in 2019. Although data from different cohorts and data sources do not allow for direct comparisons, these numbers suggest that Black students applying to medical school are disproportionately rejected at the first step compared to non-Black students. Longitudinal data collection among medical school applicants will be necessary to monitor the situation. Further studies are required to pinpoint the factors contributing to this underrepresentation, to keep improving the equity of our selection processes.